Prosocial Orientations: Distinguishing Compassionate Goals From Other Constructs - Canevello, Amy; Crocker, Jennifer (Frontiers in Psychology, 2020)
The compassionate goals scale was developed to assess the intentions underlying prosocial behaviors. Over the past 10 years, it has been shown to predict prosociality. However, research has not yet examined how compassionate goals relate to other measures of prosocial orientations or demonstrated that compassionate goals predict unique variance beyond them. Three studies addressed this shortcoming in the existing literature. Across studies, participants completed measures of compassionate goals, compassionate love, communal orientation, communion, unmitigated communion and empathic concern. Participants also reported giving to strangers (Study 1), giving to close others (Study 2). Study 3 was dyadic in nature - participants reported their reasons for giving to friends and gratitude and friends reported their gratitude toward participants. Despite strong correlations between the compassionate goals scale and other prosocial orientation measures, compassionate goals items are empirically distinct from items assessing other prosocial orientations. The compassionate goals measure accounts for unique variance in giving, reasons for giving, and gratitude. Path analyses support a dyadic process - that compassionate goals predict more other-focused reasons for giving, which then predict friends’ gratitude toward participants. While the compassionate goals measure does overlap with other well-establish and commonly used measures of prosocial orientation measures, it accounts for unique variance in giving-related outcomes, suggesting that intentions are an important aspect of prosocial orientations.